2022
DOI: 10.33963/kp.a2022.0194
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes mellitus on the diagnostic performance of fractional flow reserve in patients with severe aortic stenosis

Abstract: Background:The validity of functional assessment of coronary artery disease with fractional flow reserve (FFR) and/or instantaneous wave-free ratio (iFR) in patients with severe aortic stenosis (AS) might be affected by AS per se and other factors, including diabetes mellitus. Aims:We aimed to evaluate the impact of diabetic status on FFR performance in severe AS. Methods:The functional significance of 416 stenoses of intermediate angiographic severity in 221 patients with severe AS was assessed with iFR and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In our opinion, the article by Dziewierz et al [15] provides good data that expands our knowledge of a frequent and complex clinical problem, such as the evaluation of the severity of CAD in patients undergoing TAVI, and that can help to shed light on this relevant clinical conundrum.…”
Section: Ffr and Ifr In The Assessment Of Myocardial Ischemia In Tavimentioning
confidence: 84%
See 1 more Smart Citation
“…In our opinion, the article by Dziewierz et al [15] provides good data that expands our knowledge of a frequent and complex clinical problem, such as the evaluation of the severity of CAD in patients undergoing TAVI, and that can help to shed light on this relevant clinical conundrum.…”
Section: Ffr and Ifr In The Assessment Of Myocardial Ischemia In Tavimentioning
confidence: 84%
“…In this issue of Kardiologia Polska (Kardiol Pol, Polish Heart Journal), we can read the article by Dziewierz et al [15] that goes further in evaluating the impact of T2DM on the performance of FFR in patients with severe DAS un-dergoing TAVI. They studied the functional significance of 416 angiographically intermediate coronary lesions using iFR and FFR in 221 patients (32.1% with T2DM) with severe DAS.…”
Section: Ffr and Ifr In The Assessment Of Myocardial Ischemia In Tavimentioning
confidence: 99%
“…For instance, the FREAK study found a higher percentage of negative FFR values in patients with chronic kidney disease, suggesting a link between FFR results and creatinine levels [31]. Similarly, diabetes mellitus is often associated with diffuse vascular dysfunction in both large and micro-vessels [7,18,[32][33][34][35]. Women have a longer life expectancy than men, so they are more likely to experience other age-related diseases, such as severe aortic stenosis [36].…”
Section: Discussionmentioning
confidence: 99%
“…Women have a longer life expectancy than men, so they are more likely to experience other age-related diseases, such as severe aortic stenosis [36]. Notably, in patients with severe aortic stenosis, FFR and iFR/RFR values may be affected by a falsely low aortic pressure due to the restricted orifice of the aortic valve [7,16]. Furthermore, a reduced vasodilation ability in patients with severe aortic stenosis may result from myocardial hypertrophy, microvascular dysfunction, and elevated left ventricular end-diastolic pressure [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation